Iodine-induced hyperthyroidism: Do you mind? - Sengul, Ilker; Sengul, Demet; Pelikán, Anton (Sanamed, 2020)
Iodine can be obtained by consumption of the foods that include it or to which it is added. Iodine-induced hyperthyroidism, also known as Jod-Basedow Syndrome, usually rise in the cases of underlying thyroid disease, such as autoimmune thyroid disease, latent Graves disease, non-toxic diffuse or nodular goiter or previous thyroid surgery. Iodine-induced hyperthyroidism is frequently self-limited with a period of 1-18 months after the discontinuanceation of iodine supply/replation. The prognosis is frequently favorable, the majority returns to the baseline hormonal status. The long-term outcomes of Jod-Basedow effects remain unknown due to the scarcity of phenomenon. Nonetheless, it is remarkable that treatment, devoted to the underlying thyroid diseases, should be addressed after resolution of the acute episode. Furthermore, an interprofessional health care team must serve and officiate not only to treat iodine-induced hyperthyroidism, but also to concern themselves actively in prophylaxis.